Balanço hídrico climatológico espectral aplicado a bacia do Rio Pardo - SP - Levyman, Leonardo Auge [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
In the last years, geotechnology has been emphasizing in several areas of knowledge, becoming an indispensable tool for the monitoring and studies of small and large territorial portions. The use of orbital images and geoprocessing techniques have proven to be able to combine different types of data and generate new cartographic products, these integrated products can be used in the specific case of the Hydrographic Basins. When considering environmental conditions, water demand should be analyzed in conjunction with basin studies, quantifying the entry and exit of a certain portion of the soil over a given time interval. Thus, the objective of this research was to test the Climatological Water Balance of Thorntwaite and Matter (1955), using spectral data, applied in the Rio Pardo Hydrographic Basin -SP. The period analyzed was the years 2010 to 2016 and the data were obtained using the global ECMWF model. The Water Balance was tested by spectral variables (temperature and precipitation) and validated with field data from surface meteorological stations. The data were specialized indicating areas with water deficits and surpluses within the analyzed basin, The results were satisfactory when compared with estimated data with observed values presenting high Wilmott d index. It was possible to observe important results for the Pardo River Basin, such as the identification of regions of deficiencies and surpluses within the basin area, showing the regions most affected by these changes in the accumulation and storage of soil water. The coverage of conventional meteorological stations does not cover large areas and has only data in its surroundings, while the Spectral Water Balance will bring a regional approach to analysis

Nos últimos anos a geotecnologia vem se destacando em várias áreas do conhecimento, se tornando uma ferramenta indispensável para o monitoramento e estudos de pequenas e grandes porções territoriais. A utilização de imagens orbitais e técnicas de geoprocessamento têm se mostrado competentes para combinar diferentes tipos de dados e gerar novos produtos cartográficos, esses produtos integrados podem ser utilizados no caso específico das Bacias Hidrográficas. Quando se considera as condições do meio ambiente, a demanda da água deve ser analisada conjuntamente aos estudos das Bacias, quantificando a entrada e a saída de uma certa porção do solo em um determinado intervalo de tempo. Desta forma, o objetivo dessa pesquisa foi aplicar o Balanço Hídrico Climatológico de Thorntwaite e Matter (1955), utilizando dados espectrais, aplicados na Bacia Hidrográfica do Rio Pardo -SP. O período analisado foram os anos de 2010 a 2016 e os dados foram obtidos por meio de um modelo meteorológico global. O Balanço Hídrico foi testado por meio das variáveis espectrais (temperatura e precipitação) e validado com dados de campo das estações meteorológicas de superfície. Os dados foram espacializados indicando áreas com déficits e excedentes hídricos dentro da bacia analisada. Os resultados foram satisfatórios quando comparado dados estimados com observados apresentando alto valor do índice d de Wilmott. Foi possível identificar regiões de deficiências e excedentes dentro da área da Bacia, mostrando as regiões mais impactadas com essas mudanças do acumulo e armazenamento da água do solo. A cobertura de estações meteorológicas convencionais não abrange grandes áreas e dispõe apenas de dados em seu entorno, ao passo que o Balanço hídrico espectral apresenta uma abordagem regional de análise
Keywords: Balanço hidrológico; Climatologia; Pardo, Rio (MG e SP)